2009
DOI: 10.1007/dcr.0b013e3181a0d932
|View full text |Cite
|
Sign up to set email alerts
|

Sacrectomy for Primary Sacral Tumors

Abstract: Sacrectomy for primary sacral tumors can be safely conducted, achieving tumor-free margins and acceptable functional and long-term outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 19 publications
1
30
1
1
Order By: Relevance
“…Three cases dead during the hospitalization, another one successively for recurrence and seven patients are actually alive (four free of disease, one with persistence of the disease, two with local recurrence and one with lung metastasis); the average follow-up is 10 years and 2 months. Several authors in particular case prefer to remove the tumor by just one approach nevertheless this solution is technically more difficult so that it is suggested only for very expert surgeons [3][4][5].…”
Section: Resultsmentioning
confidence: 98%
“…Three cases dead during the hospitalization, another one successively for recurrence and seven patients are actually alive (four free of disease, one with persistence of the disease, two with local recurrence and one with lung metastasis); the average follow-up is 10 years and 2 months. Several authors in particular case prefer to remove the tumor by just one approach nevertheless this solution is technically more difficult so that it is suggested only for very expert surgeons [3][4][5].…”
Section: Resultsmentioning
confidence: 98%
“…Many authors have reported a mean intraoperative blood loss greater than 6000 ml, making it difficult to achieve wide resection due to an obstructed view, and leading to hemorrhagic shock and death. 14,25,28,32 Preoperative selective embolization of sacral tumors has proved to be an effective method for minimizing intraoperative blood loss, which will improve the safety of the operation and the resectability of sacral tumors. 27,43 We also applied an aortic balloon to decrease intraoperative blood loss, by inserting it into the abdominal artery via femoral access.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, in another observational study of 60 patients, the average number of transfused units was 5.2; however, these patients underwent preoperative tumor embolization [140]. It is important to note that the highest number of PRBCs transfused was in patients undergoing hemisacrectomies, with 75% of them receiving 10 or more units of blood [134,139]. Thus, massive blood transfusions are common in patients undergoing sacrectomies.…”
Section: Oncological Spine and Sacral Surgerymentioning
confidence: 96%
“…A few authors have successfully utilized aortic balloon occlusion to avoid significant bleeding [46,137,138]. Others have reported encouraging results with preoperative tumor embolization, ligation of both internal iliac vessels, and staged surgery [139][140][141].…”
Section: Oncological Spine and Sacral Surgerymentioning
confidence: 99%